Interaction of climate change, potentially toxic elements (PTEs), and topography on plant diversity and ecosystem functions in a high-altitude mountainous region of the Tibetan Plateau. (July 2021) - Lu, Jingzhao; Lu, Hongwei; Brusseau, Mark L.; He, Li; Gorlier, Alessandra; Yao, Tianci; Tian, Peipei; Feng, Sansan; Yu, Qing; Nie, Qianwen; Yang, Yiyang; Yin, Chuang; et al.
Abstract: Potentially toxic elements (PTEs) generated from mining activities have affected ecological diversity and ecosystem functions around the world. Accurately assessing the long-term effects of PTEs is critical to classifying recoverable areas and proposing management strategies. Mining activities that shape geographical patterns of biodiversity in individual regions are increasingly understood, but the complex interactions on broad scales and in changing environments are still unclear. In this study, we developed a series of empirical models that simulate the changes in biodiversity and ecosystem functions in mine-affected regions along elevation gradients (1500–3600 m a.s.l) in the metal-rich Qilian Mountains (∼800 km) on the northeastern Tibetan Plateau (China). Our results confirmed the crucial role of PTEs dispersal, topography, and climatic heterogeneity in the diversification of plant community composition. On average, 54% of the changes in ecosystem functions were explained by the interactions among topography, climate, and PTEs. However, merely 30% of the changes were correlated with a single driver. The changes in species composition (explained variables = 94.8%) in the PTE-polluted habitats located in the warm and humid low-elevation deserts and grasslands were greater than those occurring in the dry alpine deserts and grasslands. The ecosystem functions (soil characteristics, nutrient migration, and plant biomass) experienced greater changes in the humid low-elevation grasslands and alpine deserts. Our results suggest that the processes driven by climate or other factors can result in high-altitude PTE-affected habitat facing greater threats. Highlights: The diffusion of PTEs can unevenly affect plants diversity. Ecosystem functions (ESF) of mining area is affected by topography, climate, and PTEs. The change of soil-mediated ESFs is greater than that of plant-mediated ESFs. The ESFs in PTE-polluted habitats of lowland has experienced greater changes.